Gödelmann’s Faustus (1591). Concerning the Fluidity of the Early Transmission of the Adventures of Faustus in Germany (Studia theodisca, 2016)
This article is the first to treat systematically the brief, contemporary references to the Fauststoff in the treatise De magis, veneficis et lamiis (1591) by Johann Georg Gödelmann, best known as a witchcraft theorist. He treats Johann Faustus as a “praedestigiator”, a black magician and trickster who belongs in the company of Simon Magus. Comparing Gödelmann’s versions of the adventures of Faustus with those in the chapbook, Historia von D. Johann Fausten (1587), published in the same city (Frankfurt am Main), one sees that these adventures were in flux in the late sixteenth century.